The Effect of Caterpillar Game on Higher Order Thinking Skills (HOTS) in Early Childhood Education - Mamonto, Muzdalifa; Utoyo, Setiyo; Sutisna, Icam (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2022)
Purpose – This study aimed to determine the effect of the caterpillar game on Higher Order Thinking Skills (HOTS) in children aged 5-6 years at TK Negeri Pembina Ki Hajar Dewantoro, Dungingi District, Gorontalo City.Design/methods/approach – The research uses experimental quantitative with pre-experimental type one grub pre-test and post-test. Data analysis used the Shapiro-Wilk normality test, followed by a t-test using SPPS software. Research respondents consisted of 30 children.Findings – The findings of this study resulted in an analysis of the value of the tcount amounted to 3,689. While the value of the ttable (α) = 0.05, which equals 0.674. If tcount >ttable 3.689 >0.674, in other words, tcount > ttable, then H 0 rejected and H 1 received. So that there is an influence between the caterpillar game on the ability of Higher Order Thinking Skills (HOTS) in children aged 5-6 years at the State Kindergarten of Pembina Ki Hajar Dewantoro, Dungingi District, Gorontalo City.Research implications/limitations – This study focuses on children aged 5-6, the activity, and how the child completes the task correctly. In the learning process, some children are still challenged in their level of understanding, so there is a need for proper implementation of learning.Practical implications – This research contributes in the form of innovations to teachers in providing fun learning and references for the teaching team in developing learning media for children.Originality/value – This research provides an in-depth understanding of learning media innovation and developing Higher Order Thinking Skills (HOTS) on early childhood education.Paper type: Research paper